URGENSI PENDIDIKAN BELA NEGARA GUNA MEMBANGUN SIKAP NASIONALISME PADA GENERASI MILLENIAL DI INDONESIA - Hariswati Rachmadani Putri; Azizoel Metiadini; Hayatul Khairul Rahmat; Arifuddin Ukhsan (Universitas Muhammadiyah Tapanuli Selatan, 2020)
This paper aims to explain the urgency of state defense education in order to build an attitude of nationalism in the millennial generation in Indonesia. The research method used is the literature method with content analysis techniques. The findings of this research are that the threats that will be faced by the state in the future will not only be in the form of military threats, but more complex than that, the non-military threats that can erode the sense of nationalism of the nation's next millennial generation. Indeed, the future of this nation is in the hands of the current millennial generation. The importance of policy makers and educators in providing the widest opportunity so that they will be more motivated in terms of innovation and creativity to make their own country proud. In addition, the importance of state defense education is also contained in several hadiths and verses that support someone who loves his homeland, is willing to be ready to defend the sovereignty and honor of his nation (or better understood by jihad), and is able to make his nation proud with positive things. Hopefully, by packaging the provision of state defense education in a more neat and innovative way so that the millennial generation is better able to understand in depth what defending the country is, the importance of nationalism for state sovereignty, and its relation to religious life.